The impact of financial inclusion on the competitive advantage of Islamic banks: a case study of a sample of Al Salam Bank customers Algeria) - Daoud, ayoub (Journal of Research in Finance and Accounting, 2025)
This study aimed to clarify the impact of applying the financial inclusion on the competitive advantage of Islamic banks, Al Salam bank as a model. This study relied on the questionnaire to collect information of (300) individuals. The study reached several results, the most important is the implementation of the financial inclusion at Al Salam Bank Algeria with its dimensions had a statistically significant positive impact at the significance level of (0.05) on the level of competitive advantage explained (53.1%) of the changes.